Long and short duration pulse performance of zinc oxide varistor compacted with modified pressing cycle - Karim, A.N. Mustafizul; Puyane, R.; El-Baradie, M.A; Hashmi, M. S. J. (1996)
Zinc oxide varistor blocks are commonly pressed by the double action uniaxial compaction technique. The pressing cycle, similar to that followed in the case of conventional ceramic processing, composes of applying a load on the varistor powder (filled in the die by a suitable filling mechanism), accompanied by holding or dwell time at different phases of loading. This holding time in the form of pre-press dwell. press dwell and ejection delay are maintained respectively atlow pressure, at peak pressure and at no pressure prior to ejection. The dwell allows the material under compaction to rearrange and expels the trapped air or gas, thereby helping to reduce the inter and intra-particle pores. Thus this enhanced property of the green body is secured with the aim of attaining improved sintered properties of the ceramic. The present study which uses two level factorial design to assess the effect of dwell reveals that improvement in varistor performance is not achieved by randomly increasing the duraLion of dwell. Rather the varistor properties are found to be influenced by the individual as well as the interactive effects of the variables leaving scope for optimization, The investigation consisted of testing the energy absorption capability of varistors injected by a long duration pulse. and the high current performance of those subjected to a short duration pulse.